قوة المكافأة المعنویة في تنمیة روح الابداع لدى الاف ا رد - TAFAR, ZOUHIR (Finance and Business Economies Review, 2018)
This research study aims at checking the impact of reward power dimensions ( Engaging employees, Recognition of the effort of workers, Provide work environment) on creativity and innovation in the Mobilis Corporation Bechar /(Algeria). To achieve suchaim, we have conceived a questionnaire which was delivered to a random sample made of 30 employees all responses to the questionnaire have been collected the software package SPSS has been used for data analysis, and after necessary statistical discussion, we came across the following results: *The existence of statistical sing (at the significance level α = 0.05) which signifies that there is an acceptable level of creativity and innovation of the employees of the Mobilis Corporation *The existence of an impact the has a statistical significance (at the significance level of α = 0.05) for of reward power dimensions ( Engaging employees, Recognition of the effort of workers, Provide work environment) together and separately pertaining to creativity and innovation inside the Mobilis Corporation